THE REQUIRED NUMBER DETERMINATION OF MEASUREMENTS FOR ADVANCED VIBRO AND ACOUSTIC METHOD OF DIAGNOSTICS OF REINFORCED CONCRETE OF THE CONTACT ENVIRONMENT - Kuznetsov, V. H.; Poliakh, O. M. (Science and Transport Progress, 2008)
The necessary quantity of making shocks on a support by the improved vibroacoustic method of detecting defective supports of the contact electric mains has been investigated.